p53-stabilizing Agent CP-31398 Prevents Growth and Invasion of Urothelial Cancer of the Bladder in Transgenic UPII-SV40T Mice - Venkateshwar Madka; Yuting Zhang; Qian Li; Altaf Mohammed; Puneet Sindhwani; Stan Lightfoot; Xue-Re Wu; Levy Kopelovich; Chinthalapally V Rao (Neoplasia: An International Journal for Oncology Research, 2013)
The high prevalence of bladder cancer and its recurrence make it an important target for chemoprevention. About half of invasive urothelial tumors have mutations in p53. We determined the chemopreventive efficacy of a p53-stabilizing agent, CP-31398, in a transgenic UPII-SV40T mouse model of bladder transitional cell carcinoma (TCC) that strongly resembles human TCC. After genotyping, six-week-old UPII-SV40T mice (n = 30/group) were fed control (AIN-76A) or experimental diets containing 150 or 300 ppm of CP-31398 for 34 weeks. Progression of bladder cancer growth was monitored by magnetic resonance imaging. At 40 weeks of age, all mice were killed; urinary bladders were collected to determine weights, tumor incidence, and histopathology. There was a significant increase in bladder weights of transgenic versus wild-type mice (male: 140.2 mg vs 27.3 mg, P < .0001; female: 34.2 mg vs 14.8 mg, P < .0001). A significant decrease in the bladder tumor weights (by 68.6–80.2%, P < .0001 in males and by 36.9–55.3%, P < .0001 in females) was observed in CP-31398-treated mice. Invasive papillary TCC incidence was 100% in transgenic mice fed control diet. Both male and female mice exposed to CP-31398 showed inhibition of invasive TCC. CP-31398 (300 ppm) completely blocked invasion in female mice. Molecular analysis of the bladder tumors showed an increase in apoptosis markers (p53, p21, Bax, and Annexin V) with a decrease in vascular endothelial growth factor in transgenic mice fed CP-31398. These results suggest that p53-modulating agents can serve as potential chemopreventive agents for bladder TCC.